Wood fiber internally-reinforced polymer cement waterproof slurry and preparation method thereof

By introducing spiral hollow wood fibers into the polymer cement waterproof material to form a micro "anchored structure", the problem of insufficient toughness of existing materials is solved and crack resistance and mechanical properties are significantly improved.

CN119430817APending Publication Date: 2025-02-14YUNNAN XINCHENG WATERPROOF TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411852406.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing polymer cement-based waterproofing materials have insufficient toughness and weak impact and crack resistance, which limits their use range.

Method used

The waterproof slurry of internal reinforced polymer cement is used to embed the rigid cement matrix through spiral hollow wood fibers to form a micro "anchored structure" and improve mechanical properties.

Benefits of technology

It significantly improves the crack resistance and other physical and mechanical properties of waterproof coatings, enhances the compressive and flexural strength of the material, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430817A_ABST
    Figure CN119430817A_ABST
Patent Text Reader

Abstract

The invention discloses wood fiber internally-reinforced polymer cement waterproof slurry and a preparation method thereof, and relates to the field of waterproof coatings. The coating comprises a liquid material and a powder material, the liquid material comprises a polymer emulsion, a functional auxiliary agent and a spiral hollow wood fiber solution; the powder material comprises rigid cement, heavy calcium carbonate and quartz sand; the application range of the rigid polymer cement-based waterproof slurry is widened, the parameter performance of the rigid polymer cement-based waterproof slurry is improved, and the waterproof safety is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of waterproof coatings, in particular to a wood fiber internally reinforced polymer cement waterproof slurry and a preparation method thereof. Background Art

[0002] Polymer cement waterproof slurry (abbreviated as K11) is a waterproof slurry made of cement and fine aggregate as the main components, polymers and additives as modified materials, mixed in appropriate proportions. According to the Type I in "JCT 2090-2011 Polymer Cement Waterproof Slurry", the compressive strength is 12mPa and the flexural strength is 4.0mPa. It is a rare rigid waterproof material in the polymer cement-based waterproof material category. Compared with other flexible materials, the rigid K11 has a hard coating after curing, and the tiles are more firmly laid and not easy to fall off. At the same time, it has high compressive and anti-seepage capabilities. Therefore, it is widely used in waterproof and moisture-proof operations on home decoration walls.

[0003] K11 coating also has shortcomings, such as insufficient toughness, weak impact resistance and cracking resistance, and often cracks during ground operations, which restricts its scope of use. Industry scholars have improved the toughness of cement-based materials from many aspects and angles. Among them, JS coating is made of cement, stone powder and a high proportion of polymer emulsion, which greatly increases the elongation at break of waterproof coatings. Its final performance is similar to that of polymer emulsion waterproof coatings, but it is out of the category of rigid coatings; fiber-reinforced waterproof slurry mainly uses polymer fibers as reinforcing phases, such as polyester fibers. This method can effectively increase the dimensional stability of dry films, but it is counterproductive when used in K11 due to the weak interface; some scholars use cellulose for modification. Cellulose has a small molecular weight and has a good thickening and wetting effect on coatings. Excessive use will make the surface of the coating uneven after drying. Summary of the invention

[0004] The purpose of the present invention is to provide a wood fiber reinforced polymer cement waterproof slurry and a preparation method thereof, so as to broaden the application scope of the rigid polymer cement-based waterproof slurry, improve the parameter performance of the rigid polymer cement-based waterproof slurry, and thus ensure the purpose of waterproof safety.

[0005] In order to achieve the above object, the present invention adopts the following technical means: A wood fiber internally reinforced polymer cement waterproof slurry, comprising a liquid material and a powder material; The liquid material includes polymer emulsion, functional additives and spiral hollow wood fiber solution; The powder material includes rigid cement, heavy calcium carbonate and quartz sand.

[0006] Spiral hollow wood fibers are embedded in a rigid cement matrix. The spiral hollow structure of the wood fibers in the wood fiber solution can increase the degree of emulsion immersion. After curing, the cell cavity is filled, and the hollow skeleton gaps of the spiral hollow tubular cells will form a microscopic "anchoring structure" with the polymer cement slurry, effectively improving the mechanical properties.

[0007] Furthermore, the liquid material includes 55-60 parts of polymer emulsion, 0.5-1 parts of functional additives, and 35-40 parts of spiral hollow wood fiber solution, calculated by weight.

[0008] Preferably, the fiber content of the spiral hollow wood fiber solution is 5-15%.

[0009] Furthermore, the polymer emulsion is an environmentally friendly pure acrylic emulsion, and the functional additives include a defoamer, a dispersant and a bactericide.

[0010] Furthermore, the spiral hollow wood fiber solution is prepared in the following manner: A1. Powder the fir wood and sink it in distilled water to obtain wet wood powder; A2. Use the Franklin separation method to replace the wet wood powder with a dissociation solution containing a mixture of 30% hydrogen peroxide solution and glacial acetic acid in a ratio of 1:1. Continue to heat it in a water bath until the wood powder particles turn white and swell. Then remove them. A3. Put the fished wood powder into a sealed bottle, add water to shake the wood fibers to disperse them, and rinse and filter with deionized water; A4. Wrap the wood fiber with filter paper, air dry it, and dry it for later use to obtain wood fiber powder; A5. According to the fiber content of the spiral hollow wood fiber solution, the wood fiber powder is added to water, and after soaking, the mixture is stirred evenly to obtain the spiral hollow wood fiber solution.

[0011] Furthermore, the fir wood powder prepared in the present application can be used to prepare a wood fiber solution with a spiral hollow structure. By using the foaming process, the wood fiber powder can be expanded in water to maintain a spiral hollow shape.

[0012] Furthermore, in parts by weight, the powder includes 35-45 parts of rigid cement, 25-35 parts of heavy calcium carbonate and 25-35 parts of quartz sand, the rigid cement is PO42.5 silicate cement, the heavy calcium carbonate powder is 400-600 mesh powder, and the quartz sand is 40-60 mesh particles.

[0013] Furthermore, the mass ratio of the liquid material to the powder material is 1:3-5.

[0014] Ensure that the amount of powder is significantly higher than the amount of liquid, so that the entire polymer cement can be used as a rigid polymer cement. Avoid too little powder, which will make the finished product more like a flexible polymer cement, resulting in the inability to form an anchoring structure.

[0015] In addition, a method for preparing the aforementioned wood fiber internally reinforced polymer cement waterproof slurry comprises the following steps: S1. adding half of the functional additive to the polymer emulsion, stirring and then adding the spiral hollow wood fiber solution, stirring and then adding the remaining functional additive to obtain the liquid material; S2. The cement, the heavy calcium carbonate powder and the quartz powder are mixed in a ratio of 4:3:3 to obtain the powder; S3. Mixing the powder material with the liquid material.

[0016] Furthermore, in the step S3, the powder is slowly added to the liquid during stirring, the stirring speed during the process of adding the powder is 500-700 rpm, and after the powder is added, the stirring speed is reduced to 200-400 rpm.

[0017] The wood fiber reinforced rigid polymer cement prepared by the present invention has the following beneficial effects: The selected wood fiber has an average tensile strength of 530MPa per fiber. Its main component is cellulose, which contains a large number of hydroxyl groups and can effectively bond with high molecular polymer emulsion. The wood fiber also retains a spiral tubular structure with many grooves on the surface and a cavity inside, which can form a strong buckle structure with cement. Under the dual effects of chemistry and physics, the crack resistance and other physical and mechanical properties of the cured coating are greatly improved.

[0018] Wood fiber reinforced polymer cement waterproof coating saves costs. From the perspective of reducing costs and increasing efficiency, after using wood fiber as the reinforcing phase, after reducing the content of a certain amount of emulsion, it can still meet the parameter requirements of the ordinary type in the original standard, thereby effectively reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The figure is a schematic diagram of the process flow of preparing polymer cement according to the present invention.

[0020] Figure 2 The figure is a schematic diagram of the process flow of preparing spiral hollow wood fiber of the present invention. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0022] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.

[0024] Can be combined Figure 1 and Figure 2 As shown, a wood fiber reinforced polymer cement waterproof slurry comprises a liquid material and a powder material; The liquid material includes polymer emulsion, functional additives and spiral hollow wood fiber solution; The powder material includes rigid cement, heavy calcium carbonate and quartz sand.

[0025] Spiral hollow wood fibers are embedded in a rigid cement matrix. The spiral hollow structure of the wood fibers in the wood fiber solution can increase the degree of emulsion immersion. After curing, the cell cavity is filled, and the hollow skeleton gaps of the spiral hollow tubular cells will form a microscopic "anchoring structure" with the polymer cement slurry, effectively improving the mechanical properties.

[0026] Avoid using conventional wood fibers that exhibit a tubular structure. The cell wall structure of conventional wood fibers will prevent the penetration of the emulsion and reduce the binding properties of the modified wood fibers and polymer cement.

[0027] Furthermore, the liquid material includes 55-60 parts of polymer emulsion, 0.5-1 parts of functional additives, and 35-40 parts of spiral hollow wood fiber solution, calculated by weight.

[0028] Preferably, the fiber content of the spiral hollow wood fiber solution is 5-15%.

[0029] Furthermore, the polymer emulsion is an environmentally friendly pure acrylic emulsion, and the functional additives include a defoamer, a dispersant and a bactericide.

[0030] Furthermore, the spiral hollow wood fiber solution is prepared in the following manner: A1. Powder the fir wood and sink it in distilled water to obtain wet wood powder; A2. Use the Franklin separation method to replace the wet wood powder with a dissociation solution containing a mixture of 30% hydrogen peroxide solution and glacial acetic acid in a ratio of 1:1. Continue to heat it in a water bath until the wood powder particles turn white and swell. Then remove them. A3. Put the fished wood powder into a sealed bottle, add water to shake the wood fibers to disperse them, and rinse and filter with deionized water; A4. Wrap the wood fiber with filter paper, air dry it, and dry it for later use to obtain wood fiber powder; A5. According to the fiber content of the spiral hollow wood fiber solution, the wood fiber powder is added to water, and after soaking, the mixture is stirred evenly to obtain the spiral hollow wood fiber solution.

[0031] Furthermore, the fir powder prepared in the present application can be used to prepare a wood fiber solution with a spiral hollow structure. By utilizing the foaming process, the wood fiber powder can be unfolded in water to maintain a spiral hollow shape. Moreover, compared with conventional purchased wood fibers (wood fibers produced by mechanical abrasives), the fiber structure of the spiral hollow wood fibers prepared in the present application can remove a large amount of lignin wrapped on the fiber surface even without modification, thereby exposing more hydroxyl groups and effectively improving the bonding effect between the fiber and the polymer. To avoid the presence of a large amount of lignin on the surface of conventionally purchased wood fibers, the fibers are not strongly bonded in rigid polymer cement without modification, and the filler is prone to peeling.

[0032] Furthermore, in parts by weight, the powder includes 35-45 parts of rigid cement, 25-35 parts of heavy calcium carbonate and 25-35 parts of quartz sand, the rigid cement is PO42.5 silicate cement, the heavy calcium carbonate powder is 400-600 mesh powder, and the quartz sand is 40-60 mesh particles.

[0033] Since the spirally hollowed-out fir-based wood fibers prepared in the present application need to form an anchoring structure with the polymer cement matrix, and the wood fibers are relatively long, they will produce thread-binding phenomena during the foaming and stirring of the wood fibers, causing the wood fibers prepared in the present application to lose their spirally hollowed-out skeleton, thereby making it impossible to form a stable anchoring structure between the wood fibers and the rigid polymer cement.

[0034] Furthermore, the mass ratio of the liquid material to the powder material is 1:3-5.

[0035] Ensure that the amount of powder is significantly higher than the amount of liquid, so that the entire polymer cement can be used as a rigid polymer cement. Avoid too little powder, which will make the finished product more like a flexible polymer cement, resulting in the inability to form an anchoring structure.

[0036] In addition, a method for preparing the aforementioned wood fiber internally reinforced polymer cement waterproof slurry comprises the following steps: S1. adding half of the functional additive to the polymer emulsion, stirring and then adding the spiral hollow wood fiber solution, stirring and then adding the remaining functional additive to obtain the liquid material; S2. The cement, the heavy calcium carbonate powder and the quartz powder are mixed in a ratio of 4:3:3 to obtain the powder; S3. Mixing the powder material with the liquid material.

[0037] Furthermore, in the step S3, the powder is slowly added to the liquid during stirring, the stirring speed during the process of adding the powder is 500-700 rpm, and after the powder is added, the stirring speed is reduced to 200-400 rpm.

[0038] The following is an explanation in conjunction with specific implementation methods. In each embodiment, the specific components are as follows: Examples 1 to 3 are all prepared in the following manner: A1. Dry and grind the fir wood into powder, and select 40-60 mesh wood powder.

[0039] A2. Place an appropriate amount of wood powder in a beaker, add distilled water and seal it with plastic wrap. Place it in a 75℃ water bath until the sample is completely submerged.

[0040] A3. Use the Franklin separation method to replace the wet wood powder with a dissociation solution containing a mixture of 30% hydrogen peroxide solution and glacial acetic acid in a ratio of 1:1. Continue to place it in a 75℃ water bath for 6 hours until the wood powder particles turn white and swell, then remove them. A4. Put it into a sealed bottle, add water to shake the wood fibers to disperse them, rinse and filter with deionized water 5 to 6 times. A5. Wrap the fiber with filter paper, wait for air drying, and then use an oven at 105°C to remove residual hydrogen peroxide and glacial acetic acid. Take it out after 6 hours for later use.

[0041] A6. Weigh dry fiber according to the required concentration, add deionized water to soak for 6 hours, maintain at 600r / min for 2 hours and then set aside.

[0042] S1. Weigh the polymer emulsion, pour it into a stirrer, stir at 800r / min, slowly add the dispersant, fungicide and half of the defoamer in sequence while stirring, and stir for 15min after adding; S2. Add the wood fiber aqueous solution and stir for 30 minutes; S3. Add the remaining half of the defoamer into the stirrer and stir for 15 minutes to complete the liquid material for use.

[0043] S4. According to the formula, weigh the required grade 42.5 cement, heavy calcium carbonate powder and quartz powder and add them into the powder mixer in sequence. Stir at medium speed for 2 hours to prepare the powder for use.

[0044] S5. First weigh a certain weight of liquid material and pour it into the mixer, then weigh a certain weight of powder material according to the mixing ratio, slowly pour the powder material into the liquid material, stir at a speed of 600r / min, stir for 10-15min, then reduce the speed to 300r / min, stir for 5-10 minutes, and prepare the sample when there are no obvious visible bubbles in the coating.

[0045] In Comparative Example 1, the difference from Example 1 is that the spiral hollow wood fiber solution is not added, and the spiral hollow wood fiber solution is replaced by an equal amount of deionized water.

[0046] In Comparative Example 2, the difference from Example 1 is that the spiral hollow wood fiber solution is not added, and an equal amount of purchased wood fibers is used instead.

[0047] In comparative example 3, the difference from example 1 is that the ratio of liquid material to powder material is changed from 1:3 to 1:1.5, thus forming a relatively flexible polymer cement matrix.

[0048] In Comparative Example 4, the difference from Example 1 is that the spiral hollow wood fiber solution is prepared from 10-30 mesh fir powder.

[0049] All embodiments and comparative examples were tested according to the national standard GB / T 16777-2008.

[0050] Among them, the addition of spiral hollow wood fibers first enhances the material's crack resistance, achieving no cracking or peeling after 10 hours of boiling water cooking, and no cracking or peeling after 50 freeze-thaw cycles, which is much higher than the standard 168 hours and 25 times. The data shows that the spiral hollow wood fibers are well combined inside the dry film and effectively play the role of the material skeleton. The three-dimensional wood fiber skeleton plays the role of "strengthening tendons" from multiple angles and directions, forming an anchoring reinforcement with the matrix. The material's crack resistance is improved through the tensile strength of the wood fiber itself. Because the fibers contribute to the tensile effect at multiple angles, the dimensional stability of the material is greatly improved, thereby increasing the material's compressive strength from the national standard 12.0MPa to 14.2, and the flexural strength from 4.0MPa to 4.7MPa, an increase of about 18%. The untreated bonding strength of the material changed from 0.7 to 1.0. It was observed in the experiment that the main damage occurred inside the material. It can be seen that adding wood fiber does not directly enhance the viscosity, but increases the strength of the material's own dry film, which increases the destructive strength and indirectly increases the bonding strength data.

[0051] Comparative Example 2 is an experimental group using ordinary wood fiber as a reinforcing phase. The data in this group of experiments are mostly unchanged, and only the flexural strength and compressive strength are increased by about 5%. It is said that the spiral hollow wood fiber prepared in this application has a better modification effect on rigid polymer cement slurry than polyester fiber.

[0052] Comparative Example 3 transforms the polymer cement matrix from a rigid polymer cement matrix to a relatively flexible polymer cement matrix, whose flexural strength and compressive strength only meet the national standard. Therefore, in the flexible polymer cement, even if spiral hollow wood fibers are used, they cannot form an anchoring reinforcement structure with the matrix.

[0053] In Comparative Example 4, since the mesh size of the fir powder used to prepare the spiral hollow wood fiber is reduced, the fiber length is relatively large. After preparation, even if it is added to the rigid polymer cement, its spiral hollow structure is prone to a large amount of hanging wire and entanglement, which affects the emulsion immersion of the rigid polymer cement, making it difficult to form an anchoring reinforcement structure.

[0054] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A wood fiber internally reinforced polymer cement waterproof slurry, characterized in that: Including liquid and powder; The liquid material includes polymer emulsion, functional additives and spiral hollow wood fiber solution; The powder material includes rigid cement, heavy calcium carbonate and quartz sand.

2. The wood fiber internally reinforced polymer cement waterproof slurry according to claim 1, characterized in that: In parts by weight, the liquid material comprises 55-60 parts of polymer emulsion, 0.5-1 parts of functional additives, and 35-40 parts of spiral hollow wood fiber solution.

3. The wood fiber internally reinforced polymer cement waterproof slurry according to claim 2, characterized in that: The fiber content of the spiral hollow wood fiber solution is 5-15%.

4. The wood fiber internally reinforced polymer cement waterproof slurry according to claim 1, characterized in that: The polymer emulsion is an environmentally friendly pure acrylic emulsion, and the functional additives include a defoamer, a dispersant and a bactericide.

5. The wood fiber internally reinforced polymer cement waterproof slurry according to any one of claims 1 to 4, characterized in that: The spiral hollow wood fiber solution is prepared in the following manner: A1. Powder the fir wood and sink it in distilled water to obtain wet wood powder; A2. Use the Franklin separation method to replace the wet wood powder with a dissociation solution containing a mixture of 30% hydrogen peroxide solution and glacial acetic acid in a ratio of 1:

1. Continue to heat it in a water bath until the wood powder particles turn white and swell. Then remove them. A3. Put the fished wood powder into a sealed bottle, add water to shake the wood fibers to disperse them, and rinse and filter with deionized water; A4. Wrap the wood fiber with filter paper, air dry it, and dry it for later use to obtain wood fiber powder; A5. According to the fiber content of the spiral hollow wood fiber solution, the wood fiber powder is added to water, and after soaking, the mixture is stirred evenly to obtain the spiral hollow wood fiber solution.

6. The wood fiber internally reinforced polymer cement waterproof slurry according to claim 1, characterized in that: In parts by weight, the powder includes 35-45 parts of rigid cement, 25-35 parts of heavy calcium carbonate and 25-35 parts of quartz sand, the rigid cement is PO42.5 silicate cement, the heavy calcium carbonate powder is 400-600 mesh powder, and the quartz sand is 40-60 mesh particles.

7. The wood fiber internally reinforced polymer cement waterproof slurry according to claim 1, characterized in that: The mass ratio of the liquid material to the powder material is 1:3-5.

8. A method for preparing the wood fiber reinforced polymer cement waterproof slurry according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. adding half of the functional additive to the polymer emulsion, stirring and then adding the spiral hollow wood fiber solution, stirring and then adding the remaining functional additive to obtain the liquid material; S2. The cement, the heavy calcium carbonate powder and the quartz powder are mixed in a ratio of 4:3:3 to obtain the powder; S3. Mixing the powder material with the liquid material.

9. The method for preparing a wood fiber internally reinforced polymer cement waterproof slurry according to claim 8, characterized in that: In the step S3, the powder is slowly added to the liquid during stirring, the stirring speed during the process of adding the powder is 500-700 rpm, and after the powder is added, the stirring speed is reduced to 200-400 rpm.